Pembullyan Dalam Perspektif Hadits Abu Hurairah Dan Relevansi Pasal 76c Tahun 2014 - Rizki Tirta Ramadhan; Tajul Arifin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This abstract discusses the role of Abu Hurairah's hadith in the context of handling bullying, as well as the relevance of Article 76c of 2014 in modern legal efforts. This research aims to explore the Islamic understanding of hurtful behavior and the way modern law deals with similar cases. Through a text and literature analysis approach, this study dissects Abu Hurairah's views on abusive treatment and its implications in society. Furthermore, legal analysis on Article 76c of 2014 is explored to understand the legal response to bullying. The results demonstrate the complexity of blending religious views with modern law in addressing rapidly changing social issues. The suggestions from this study highlight the need for inter-religious exchange and intrigue in defining successful arrangements in addressing the issue of oppression, incorporating instructive, legal, and social viewpoints.